Prevalence of dementia and mild cognitive impairment before incarceration. Issue 6 (25th February 2022) - Kuffel, Randall L.; Byers, Amy L.; Williams, Brie; Fortinsky, Richard; Li, Yixia; Ruderman, Michael A.; Barry, Lisa C.
Abstract: Background: Accumulating evidence indicates that behaviors in Alzheimer's disease and related dementias could result in incarceration. Yet, the proportion of persons diagnosed with dementia and mild cognitive impairment (MCI) before they were incarcerated is largely unknown. By leveraging a national sample of mid‐ to late‐life adults who were incarcerated, we determined the prevalence of dementia and MCI before their incarceration. Methods: In this current study, participants were Medicare‐eligible U.S. veterans who transitioned from incarceration to the community in mid‐ to late‐life from October 1, 2012, to September 30, 2018, after having been incarcerated for ≤10 consecutive years ( N = 17, 962). Medical claims data were used to determine clinical diagnoses of dementia and MCI up to three years before incarceration. Demographics, comorbidities, and duration of incarceration among those with dementia and MCI were compared to those with neither diagnosis. Results: Participants were >97% male, 65% non‐Hispanic white, 30% non‐Hispanic black, and 3.3% had a diagnosis of either dementia (2.5%) or MCI (0.8%) before their most recent incarceration. Individuals with MCI or dementia diagnoses were older, were more likely to be non‐Hispanic white, had more medical and psychiatric comorbidities, and experienced homelessness and traumatic brain injury at higher rates than those with neither diagnosis. Average duration of incarceration was significantly shorter among those with MCI (201.8 [±248.0] days) or dementia (312.8 [±548.3] days), as compared to those with neither diagnosis (497.0 [±692.7] days) ( p < 0.001). Conclusions: These findings raise awareness of the proportion of incarcerated persons in the United States who have a diagnosis of MCI or dementia before they are incarcerated. Improved understanding of pathways linking cognitive impairment to incarceration in mid‐ to late‐life are needed to inform appropriateness of incarceration, optimization of health care, and prevention of interpersonal harm in this medically vulnerable population.